Factors Related to the Incidence of Stunting in Children in the Working Area of the Pontap Health Center, Palopo City in 2025 - Nirma Nirma; Andi Sastria Ahmad; Asriadi Asriadi; Indra Amanah AN (AACENDIKIA: Journal of Nursing, 2025)
Stress is a physical, mental, and behavioral response to the pressure people experience to adapt and manage internal and external pressures. Stress can affect anyone, including teenagers. The stress experienced by teenagers can be caused by factors such as parental parenting, family support, and feelings of loneliness in the family environment. This Research aims to determine whether factors are associated with stunting among children in the work area of the Pontap Health Center in Palopo City. This type of Research is a quantitative survey Research design with a cross-sectional approach. This Research used a purposive sampling method, with a sample of 53 respondents from the work area of the Pontap Health Center in Palopo City in 2025. The instruments of this Research were a questionnaire and the KMS book. Chi-Square in maternal knowledge Research shows a significance value of ρ=0.001; in research on maternal parenting patterns, it shows a significance value of ρ=0.001; and in socio-economic research, it shows a significance value of ρ=0.041. Mother's knowledge, mother's parenting style, and social economy are factors in the incidence of stunting in the work area of the Pontap Health Center in Palopo City in 2025.